Hubungan konsumsi makanan dan kadar hemoglobin (Hb) dengan prestasi belajar siswa SLTP Kota Palembang - Sartono Sartono; Wiryatun Lestariana; Toto Sudargo (Jurnal Gizi Klinik Indonesia, 2007)
Background: Nutrition problems may happen to all groups of ages. A problem at a particular age group may affect nutrition status of the next periodic life cycle (intergenerational impact). Malnourished children may encounter physical growth, mental and intellectual disorder. Someone’s nutrition status may be affected by food consumption supply. Nutrition status can affect children schooling and academic achievement. Children suffering from iron deficiency have lower score in cognitive growth, study and academic achievement.Objective: To identify relationship between food consumption and haemoglobin (Hb) level and academic achievement of junior high school students at Palembang Municipality.Method: The study was an analytical survey with cross sectional design. Population and samples were junior high school students at Palembang Municipality as subject of the study. Samples were chosen with multistage sampling design, the group was randomly selected and samples of each junior high school and grade were chosen using proportional stratified random sampling technique. Data analysis used univariable, bivariable and multivariable techniques. Bivariable statistical test was used to identify relationship between food consumption and academic achievement and between Hb level and academic achievement; whereas regression test was used to identify relationship between food consumption and Hb level. Meanwhile, multivariable analysis used double linear regression. Data of food consumption were processed using NutriSurvey program for Windows. All data were then processed with SPSS program version 10.Result: There was relationship between food consumption (energy, protein, vitamin C, zinc intake) and academic achievement (energy: p=0.001, r=0.372; protein: p=0.046, r=0.209; vitamin C: p=0.009, r=0.273; zinc: p=0.042, r=0.214), and there was relationship between Hb level and academic achievement (p=<0.001, r=0.421). There was relationship between food consumption (energy intake) and Hb level. (p=0.051, r=0.205).Conclusion: The result of multivariable showed that only Hb level had significant relationship with academic achievement (p=<0.001, B=2.077).